POLA PENYELARASAN RUANG PADA UNIT HUNIAN DI RUMAH SUSUN SARIJADI BANDUNG - Amirani Ritva Santoso; Gina Perris (TATANAN, 2007)
Abstract                This study examines adjustment pattern done by the occupants of low cost multi-storey housing – Sarijadi Bandung to their dwelling units that have been occupied for more than ten years. The main interest of this study was ignited by the significant degradation in Bandung’s environmental quality due to the lack of planning in horizontal urbal expansion. The vertical city development needs to be considered such as developing low cost multi-storey housing to avoid environmental degradation and improve the wealth grade of middle-low income society which is dominating the population in Indonesian big cities. Every family wants to have a home which could accomplish their basic needs and needs of self-actualization. It is not a simple task to live in small dwellings unit at a low cost multi-storey housing and neighboring with others and also sharing common space. That is why the occupants have to adapt simultaneously due to the changing of their daily activities as their lifecycle’s changing. Observation has been done by direct observation and interview with the occupants, five units each from long-type and short-type blocks. Observation focused in occupants’ change of living space pattern and daily activities rhythm, which concluded daily needs and self-actualization accomplishment. It is important to find the problem cause and its effect for daily activities rhythm and will be use for further improvement in dwelling unit’s design for a low cost multi storey housing in the future. Key words: adjustment pattern, low cost multi storey housing, Sarijadi Bandung Abstrak                Studi ini membahas tentang pola penyelarasan ruang yang dilakukan oleh penghuni Rumah Susun Sarijadi Bandung pada unit hunian yang telah dihuni selama lebih dari sepuluh tahun. Studi dilakukan karena pengembangan kota Bandung secara horisontal. Pengembangan vertikal kota perlu dipertimbangkan dan salah satu cara efektif adalah pembangunan rumah susun untuk menghindari dampak lingkungan yang lebih buruk sekaligus berguna bagi kesejahteraan masyarakat yang mayoritas menengah ke bawah. Setiap keluarga pasti mendambakan hunian yang dapat memenuhi seluruh kebutuhan dasar dan aktualisasi diri. Tidak mudah menghuni unit hunian di rumah susun sederhana dengan unit hunian lain disekelilingnya dan luas terbatas serta harus berbagi ruang bersama. Sejalan masa huni yang panjang, ritme aktivitas keseharian masing-masing anggota keluarga berkembang dan berubah sesuai siklus kehidupannya. Untuk itu penghuni perlu terus menerus melakukan penyelarasan ruang pada unit hunian. Pengamatan dilakukan melalui pengamatan langsung dan wawancara dengan penghuni, masing-masing pada lima unit hunian di blok tipe panjang dan pendek. Fokus pengamatan pada perubahan tatanan ruang dan ritme aktivitas keseharian penghuni, meliputi aktivitas pemenuhan kebutuhan dasar hingga aktualisasi diri. Hal ini akan dibahas untuk menemukan penyebab masalah dan akibatnya pada ritme keseharian penghuni dan akan dijadikan landasan pembuatan saran bagi bentuk dan tatanan unit hunian bagi rumah susun sederhana di masa mendatang. Kata Kunci:  pola penyelarasan, rumah susun, Sarijadi Bandung